SEKATEN NIGHT MARKET TOYS AND GAMES BATIK MOTIFS: AN APPLICATION FOR CHILDREN'S CASUAL CLOTHES - Ainun Nur Kholifah; Syarifah Nur Hajja (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2024)
The aims of this creation are to re-introduce the rides and games in Sekaten Night Market to children through batik motif which is be applied to children's casual clothing. The method used in this creation are exploration, design, and embodiment. The process of creating works starts from the exploration stage, namely by observing the rides and traditional sekaten games. Designing process was conducted by determining alternative designs to be selected as batik motifs that are applied to children's casual clothing through the process embodiments. The embodiment technique applied to the entire work uses the dab coloring written batik technique using remasol dye. The output in the creation of this work is in the form of four children’s casual wear that consists of two girl wears and two boy wears. In this work there are four titles of batik motif works with names “Ceplok Bianglala”, “Tambal Kora-Kora”, “Parang Otok-Otok” and “Kawung Gangsing”. Besides, there are four fashion title, namely “Kenes”, “Hasya”, “Abinaya”, and “Meraki”. The end result of the creation of this work is suitable for children's casual clothing.